Slovensko predsedovanje Svetu EU in uresničevanje nacionalnih interesov - Svetličič, Marjan (Teorija in praksa, 2012)
The main goal of the article is to establish how Slovenia defined and effectuated its national interests during its presidency of the Council of the EU. Our analysis is based on a representative questionnaire that included 235 to 407 respondents among key Slovenian presidency actors. An important aspect of our research was to assess the extent to which the Slovenian presidency was in line with the postulates of the theory of small states' presidencies. The analysis supports some of the theoretical expectations, yet it also reveals certain disparities. Our analysis confirms some theoretical predictions that a member state can promote its national interests more easily during such a presidency because it possesses certain powers that enable it to set the agenda, which is the most effective way of realising national interests. With particular reference to small state presidencies, the advocating of national interests can also be facilitated by having a smaller range of priorities and a greater level of coincidence with the interests of other key actors. The analysis of the Slovenian presidency reveals that, besides the country's size, other factors limited its ability to fulfil its national interests. In addition to a weak ability to engage in coalition building and lobbying, the two main constraining factors were namely the lack of soft skills among Slovenian officials and weak coordination among policy agents.
Keywords: EU Council Presidency; Predsedstvo Sveta EU; Agenda; Dnevni red; Slovenia; Slovenija; nacionalni interesi; majhne države; Svet EU; predsedovanje; ankete